Evaluasi Koleksi Bidang Kedokteran Umum dengan Menggunakan Metode Conspectus di UPT Perpustakaan Universitas Jenderal Soedirman Purwokerto - Supriyana Supriyana; Taftrikhudin Taftrikhudin (Jurnal Pustaka Ilmiah, 2021)
The purpose of this study was to determine the collection of books in the field of general medicine at UPT Unsoed Purwokerto Library in accordance with the process of developing the collection and to map the strengths and weaknesses of the book collection in the field of general medicine. The research methodology was conducted using quantitative methods with a descriptive approach. Research data are textbooks with general medical subjects. Research data were collected by observation, documentation, collection evaluation questionnaire with conspectus and interview indicator standards. Population sampling and research sample based on the Krecjie table. While the data analysis technique is by collecting conspectus sheets, tabulations and percentages from each subject distribution. The results showed the level of depth of the collection of general medicine in UPT Purwokerto Unsoed Library in the range of 1a to 3. This means that collections in the field of public medicine at UPT Unsoed Library have supported the department of general medicine. The highest distribution of subjects was in the subject of disease science namely class number 616.1-616.9 a number of 87 collection titles. Analysis of general medical field language coverage for each class number is dominated by Indonesian. As for the chronological coverage of the field of general medicine it is said to be quite relevant to the latest information needs. Literature material published in the last five years totaling 58 collection titles or 20%. The collection of general medicine is dominated by the 2000-2009 published year with 118 titles with a percentage of 41% and the collection with the year published <1990 with 55 titles reaching 16%. Conclusion: UPT Unsoed Library immediately compiled a collection development policy manual as a guide in developing collections and establishing more intensive communication with the visitors.